The Effectiveness of Shaping Techniques in Improving Independence in Genital Hygiene Among Students with Moderate Intellectual Disabilities - Galih Gustiana Wijaya; Budi Susetyo; Iding Tarsidi (Eduvest - Journal of Universal Studies, 2026)
Health in the reproductive organs is important for adolescents, including children with disabilities. Although disabled children have shortcomings and limitations in terms of their intellect, they require independence in taking care of personal needs, especially in terms of maintaining the cleanliness of the reproductive organs. Interventions are needed that can encourage the independence of personal hygiene skills of genitalia of children with disabilities. One of the alternative behavior modifications that can be applied to increase the independence of children with disabilities is shaping. This study aims to increase the independence of personal hygiene genitalia of students with moderate disabilities at SLB Satria Galdin. The method used was Single Subject Research with an A-B-A design. Data is collected through performance tests using test instruments. The data obtained was analyzed using descriptive statistical analysis and displayed in simple line graphs. The results of this study showed an increase in independence in students in genitalia personal hygiene skills, evidenced by an increase in the mean level in conditions at baseline 1 (A-1) by 54.10%, intervention (B) by 62.70% and baseline 2 (A-2) by 78.70%. Based on these results, it can be concluded that the shaping technique is effective in increasing the independence of genitalia personal hygiene in students with moderate intellectual disabilities, as demonstrated by the progressive improvement across all phases with zero percentage overlap between baseline and intervention phases, indicating that the intervention had a positive and meaningful impact on the target behavior.